2006
DOI: 10.1177/0009922806294219
|View full text |Cite
|
Sign up to set email alerts
|

Atomoxetine in the Management of Children with ADHD: Effects on Quality of Life and School Functioning

Abstract: The purpose of this study was to examine in a controlled trial the effects of atomoxetine on the management of attention deficit-hyperactivity disorder (ADHD) symptoms and functional impairments at school and at home. Participants were 153 children (age 8 to 12 years) diagnosed with attention-deficit hyperactivity disorder who were randomized to double-blind treatment with either atomoxetine (n = 101) or placebo (n = 52). Findings revealed significant improvements both for parent and teacher ratings of behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 16 publications
0
46
0
Order By: Relevance
“…During the development of the parent version of the Child Health Questionnaire (CHQ-PF50), Landgraf et al [42] reported that an ADHD sample were rated as having significantly lower scores on the psychosocial summary score and the psychosocial and family subscales (behaviour, mental health, self-esteem, role limitations-emotional/behavioural, parental impact-emotional and time, family activities and family cohesion), compared to their norm group. These findings were replicated in several clinical ADHD samples which used the CHQ and compared children with ADHD to either healthy controls [26, 32, 75] or US norms [15, 38, 39, 45, 46, 52, 57, 58, 64, 97]. Differences have been reported for both male and female subjects.…”
Section: What Is the Impact Of Adhd On Qol?mentioning
confidence: 69%
See 1 more Smart Citation
“…During the development of the parent version of the Child Health Questionnaire (CHQ-PF50), Landgraf et al [42] reported that an ADHD sample were rated as having significantly lower scores on the psychosocial summary score and the psychosocial and family subscales (behaviour, mental health, self-esteem, role limitations-emotional/behavioural, parental impact-emotional and time, family activities and family cohesion), compared to their norm group. These findings were replicated in several clinical ADHD samples which used the CHQ and compared children with ADHD to either healthy controls [26, 32, 75] or US norms [15, 38, 39, 45, 46, 52, 57, 58, 64, 97]. Differences have been reported for both male and female subjects.…”
Section: What Is the Impact Of Adhd On Qol?mentioning
confidence: 69%
“…Placebo)CHQParent293 ADHD, 39% with ODD8 weeksYouths with ADHD and comorbid ODD showed greater improvement in QoL on ATX than placebo. Treatment response was similar in youths with and without ODD, except that the comorbid group only improved at higher doses Brown et al [15]RCT (ATX vs. Placebo)CHQParent1537 weeksParent reported QoL demonstrated a trend toward better response to ATX than to placebo Perwien et al [58]Open label trial; extension of RCTs (ATX)CHQParent912 ADHD, 312 completed long term trial and included in outcome analyses24 monthsSignificant improvements were observed on the psychosocial summary scale, and all psychosocial domains but not the physical health domains following acute treatment with atomoxetine.…”
Section: Resultsmentioning
confidence: 95%
“…For example, the QoL of children and adolescents with ADHD has been shown to improve over time when on medication [16,18,[93][94][95][96][97][98][99]. More specifically, a number of studies have shown the improvement of self-esteem in children and adolescents with treatment for ADHD.…”
Section: Impact On Quality Of Lifementioning
confidence: 99%
“…[19][20][21][22][23][24][25][26] Atomoxetine also demonstrated efficacy in the longer term treatment of these patients. [27,28] A single morning dose was shown to be effective into the evening, [21,26] and discontinuation of atomoxetine was not associated with symptom rebound.…”
Section: Therapeutic Efficacymentioning
confidence: 99%
“…[17] The majority of adverse events were mild or moderate; [34][35][36]38,40] there was a very low incidence of serious adverse events. [19,[21][22][23][24][25][26][27][28]33,35,[37][38][39][40][41]43,44] Few patients discontinued atomoxetine treatment because of adverse events. [17] Atomoxetine discontinuation appeared to be well tolerated, with a low incidence of discontinuation-emergent adverse events.…”
Section: Tolerabilitymentioning
confidence: 99%